Synergistic effects of hybrid polypropylene and steel fibers on explosive spalling prevention of ultra-high performance concrete at elevated temperature - Li, Ye (2020)
This study investigated synergetic effects of hybrid polypropylene (PP) and steel fibers on explosive spalling prevention of ultra-high performance concrete (UHPC) at elevated temperature. Permeability of UHPC was measured and correlated to the extent of spalling quantitatively. Microstructures of UHPC before and after elevated temperature exposure were examined to reveal potential mechanisms responsible for changes in permeability. Results showed that the use of hybrid PP and steel fibers completely prevented explosive spalling even at low fiber dosage of both fibers due to significant increase of permeability. Microstructural analysis revealed that such synergistic effect on increased permeability of hybrid PP and steel fiber-reinforced UHPC was attributed to enhanced connectivity of empty PP fiber tunnels by multiple microcracks generated from the thermal expansion of both fibers.